Jpeg/Exif Message Digest Compilation With SHA512 Hash Function - fitriyanto, rachmad (CSRID (Computer Science Research and Its Development Journal), 2019)
Security information method for jpeg / exif documents generally aims to prevent security attack by protecting documents with password and watermark. Both methods cannot used to determine the condition of data integrity at the detection stage of the information security cycle. Message Digest is the essence of a file that used to represent data integrity. This study aims to compile a message digest to detect changes that occur in jpeg / exif documents in information security. The research phase consists of five stages. The first stage, identification of the jpeg / exif document structure conducted using Boyer-Moore string matching algorithm to find jpeg/exif segments location. The Second stage is segment content acquisition, conducted based on segment location and length obtained. The Third step, computing message digest for each segment using SHA512 hash function. Fourth stage, jpeg / exif document modification experiments to identified affected segments. The Fifth stage is selecting and combining the hash value of the segment into message digest. Obtained result show message digest for jpeg / exif documents composed of two parts, the hash value of the SOI segment and the APP1 segment. The SOI segment value used to detect modifications for jpeg to png conversion and image editing. The APP1 hash value used to detect metadata editing. The SOF0 hash values use to detect modification for image recoloring, cropping and resizing.